READING INTEREST AND LITERATURE OF THE TEACHERS OF ISLAMIC RELIGIOUS EDUCATION IN SENIOR HIGH SCHOOL IN TANGERANG CITY, BANTEN - Asep Saefulloh (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2018)
English This paper discusses reading materials on religious topics consumed by the teachers of Islamic Religious Subject (Pendidikan Agama Islam [PAI]) in Senior High School (Sekolah Menengah Atas [SMA]) in Tangerang City, Banten Province. The teachers seem not to take benefit from Religious books as enriching literatures for the teaching of Islamic education materials. To glean the data, the study used questionnaires and interviews. The respondents of the study were 28 teachers of PAI. The study found that there were mainly two titles of the religious literatures commonly used by the teachers: Fiqh Sunnah, by Sayyid Sabiq, was mentioned 10 times, and Fiqh Islam, by Sulaiman Rashid was mentioned seven times. The study disclosed the facts that the teachers have no sufficient literatures on the studies of Qur’an, Hadith, Aqidah, Morals, and History of Islamic Culture. These areas were only mentioned once at average. The issue of “reading interest,” may be “low” in the context of enriching the subject materials, but it was “quite high” when associated with religious knowledge enrichment for everyday life. Indonesia Tulisan ini membahas tema bahan bacaan keagamaan guru mata pelajaran Pendidikan Agama Islam (PAI) SMA di Kota Tangerang Banten. Buku bacaan keagamaan sebagai literatur pengayaan bagi para guru PAI SMA, khususnya di Kota Tangerang Banten tergolong masih sedikit dimanfaatkan. Metode pengumpulan data digunakan angket dan wawancara. Jumlah responden sebanyak 28 orang guru PAI. Dari data yang diperoleh diketahui bahwa buku bacaan keagamaan yang relatif sering disebutkan hanya dua judul, dan keduanya untuk materi pembahasan fikih, yaitu Fiqih Sunnah, karya Sayyid Sabiq, disebutkan 10 kali, dan Fiqih Islam, karya Sulaiman Rasyid disebutkan tujuh kali. Temuan lain adalah minimnya referensi untuk materi-materi Al-Qur’an, Hadis, Akidah, Akhlak, dan Sejarah Kebudayaan Islam (SKI), rata-rata hanya disebutkan satu kali. Persoalan “minat baca”, bisa jadi “minim” dalam konteks memperkaya wawasan untuk menambah materi pembahasan mata pelajaran PAI, tetapi “cukup tinggi” jika dikaitkan dengan penambahan pengetahuan agama untuk kehidupan sehari-hari.